2019
DOI: 10.1097/aud.0000000000000727
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effectiveness of Bimodal Stimulation Compared to Unilateral and Bilateral Cochlear Implant Use in Adults with Bilateral Severe to Profound Deafness

Abstract: CT and CAF declare no conflicts of interest. PTK's institution has received research grants from manufacturers of cochlear implants and hearing aids to support research projects not directly related to the current work. PTK has carried out consultancy work for Phonak Ltd., a manufacturer of hearing aids, unrelated to the current work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
1
6
0
1
Order By: Relevance
“…This remarkable additional improvement was seen in all subdomains of the NCIQ: primary sound perception, advanced sound perception, speech production, self-esteem, activity, and social interactions. Our results corroborate these of others [ 10 , 12 , 23 ] and fully justify the medical effort.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This remarkable additional improvement was seen in all subdomains of the NCIQ: primary sound perception, advanced sound perception, speech production, self-esteem, activity, and social interactions. Our results corroborate these of others [ 10 , 12 , 23 ] and fully justify the medical effort.…”
Section: Discussionsupporting
confidence: 92%
“…The theoretically potential disadvantages include bilateral vestibular alterations, surgical complications, and cost [6][7][8]. The debate about cost-effectiveness is particularly controversial [9][10][11]. Up to this point, most research investigating bilateral CI supply has focused on auditory improvement, including sound localisation and enhanced speech perception, but little is known about the subjectively experienced changes created by a CI, and very few studies have analysed the health-specific quality of life changes due to a second CI [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Faced with a range of estimates of varying quality, systematic reviews have concluded that the gain in HRQL associated with bilateral compared with unilateral implantation is sufficiently small (0.03, Bond et al 2009;0.035, Health Quality Ontario 2018) to prompt uncertainty about whether bilateral implantation gains sufficient additional QALYs to justify its costs (Bond et al 2009;Lammers et al 2011;Health Quality Ontario 2018;Theriou et al 2019). Analysts have reached those conclusions both when they have decided on balance that bilateral implantation is a TABLE 1.…”
Section: Introductionmentioning
confidence: 99%
“…Batched citations. 9,17-20,23,27,30-32,37,39,42-48,51,52,54,55,57,58,60,62,65,66,68,69,73-77,82-84,88,91,92,95,98,99,103,105,109,113,114,117,120-123,125,127-131][ 16,26,28,36,38,40,49,56,59,63,64,[70][71][72]79,81,85,86,89,90,93,94,96,97,[100][101][102]104,106,107,110,111] …”
mentioning
confidence: 99%